education - Lidin, Konstantin (project baikal, 2020)
The rapid development of the Internet blurs the geographical concept of province. In the “space of the worldwide web”, centers emerge, become influential and then lose their status so quickly that they simply have no time to become a metropolis. Architectural education experiences these trends to the full extent. The global crisis of the educational system has created a strong demand for distant forms of the professional training; while the coronavirus pandemic has boosted the development of online education. The themes of students’ projects are also changing: provincial cities have become a popular topic for students of metropolitan universities. Even campus architecture is under the pervasive influence of the Internet. The collection of articles devoted to the problems and prospects of the development of architectural education in the new context brings up the topic that will be continued in our next issues.